Turkey’s response to post cold-war international crises in the context of her relations with the EU - Gözkaman, Armağan (My University, 2010)
Bu çalışmanın ana hedefi, Türkiye ile Avrupa Birliği’nin küresel platformdaki temel sorunlarla mücadelelerindeki uyumluluğu, özellikle uluslararası krizleri mercek altına alarak, araştırmaktı. Bu amaçla, ilk ana bölümde kavramsal ve tarihsel arka plana yer verilmiştir. İlk olarak uluslararası krizin ve ilgili kavramların tanımı - tarihsel süreç de ortaya konarak – verimiş, daha sonra da Türkiye'nin ve AB'nin krizlere verdikleri tepkilerde paralellik oluşmasını sağlayan faktörler incelenmiştir. Son bölümde bu iki aktörün kriz yönetimiyle ilgili olarak geçirdikleri tarihsel evrim, NATO’ya da yer vererek incelenmiştir. İkinci ana bölümün ana araştırma temasını, bu iki aktörün olgusal uyumunu araştırma teşkil etmiştir. Bu çaba, üç bölüm aracılığıyla somutlaşmıştır. Birinci bölümde diplomatik girişimler incelenmiş, ikinci bölümde ise operasyonel alandaki paralellik ve farklılıklara odaklanılmıştır. Çalışmanın son kısmı, Türk dış politikası açısından önem taşıyan Kıbrıs ve Irak vakalarının incelenmesine ayrılmıştır. Uluslararası kriz, Türkiye, Avrupa Birliği, dış politika

The main goal of the study has been to seek whether there is a compatibility between Turkey and the European Union (EU) in meeting the key challenges in the global platform, with a special focus on the international crises. With this purpose, the first part has been allotted to the conceptual and historical background. It began with an effort to define the international crisis (and the concepts derived from it) by presenting a historical development. Then, the factors that provide a parallelism for Turkey’s and the EU’s reactions to crises have been explored. The last chapter was related to the historical evolution of crisis management in these two polities by according a place to NATO. In the second part, factual compatibility of action between the two actors constituted the main research theme. This effort has been materialized through three chapters. At first, diplomatic initiatives have been exposed. The second area of focus concerned the parallelism and divergences in the operational field. Last, the following two cases have been studied because of the particular importance that they have for Turkish foreign policy: Cyprus and Iraq. International Crisis, Turkey, European Union, Foreign Policy
Keywords: Avrupa Birliği; Kriz_Avrupa Birliği; Uluslararası İlişkiler